Design And Verification Of The Strength Level Of The Proposed New Type Of Columns (Diversity Research: Journal of Analysis and Trends, 2025)
In the article, work was carried out on improving the grate, which is the main part of cleaning machines used to separate impurities from cotton during the primary processing of cotton, and design and strength calculations were carried out using modern programs. According to the design results, the proposed hexagonal grate bars can be used in practice, i.e., they fully meet the requirements for strength and durability. As a result, the introduction of such structures into production not only increases the efficiency of cleaning devices but also ensures their reliability.